Cellular miR-150-5p may have a crucial role to play in the biology of SARS-CoV-2 infection by regulating nsp10 gene. Issue 1 (31st December 2022) - Akula, Shaw M.; Bolin, Paul; Cook, Paul P.
ABSTRACT: The role for circulating miRNAs as biomarkers of the COVID-19 disease remains uncertain. We analysed the circulating miRNA profile in twelve COVID-19 patients with moderate-severe disease. This analysis was conducted by performing next generation sequencing (NGS) followed by real-time polymerase chain reaction (RT-qPCR). Compared with healthy controls, we detected significant changes in the circulating miRNA profile of COVID-19 patients. The miRNAs that were significantly altered in all the COVID-19 patients were miR-150-5p, miR-375, miR-122-5p, miR-494-3p, miR-3197, miR-4690-5p, miR-1915-3p, and miR-3652. Infection assays performed using miRNA mimics in HEK-293 T cells determined miR-150-5p to have a crucial role in SARS-CoV-2 infection and this was based on the following data: (i) miR-150-5p mimic lowered in vitro SARS-CoV-2 infection; (ii) miR-150-5p inhibitor reversed the effects of miR-150-5p mimic on SARS-CoV-2 infection of cells; and (iii) a novel miRNA recognition element (MRE) was identified in the coding strand of SARS-CoV-2 nsp10, the expression of which could be inhibited by miR-150-5p mimic. Our findings identified crucial miRNA footprints in COVID-19 patients with moderate-severe disease. A combination of co-transfection and Western blotting experiments also determined the ability of miR-150-5p to inhibit SARS-CoV-2 infection via directly interacting with MRE in the coding strand of nsp10 . Our investigation showed that a sharp decline in the miR-150-5p plasma levels in COVID-19 patients may support enhanced SARS-CoV-2 infection. Furthermore, this study provides insight into one possible mechanism by which COVID-19-induced changes to miR-150-5p levels may promote SARS-CoV-2 infection via modulating nsp10 expression.